Toxoplasma gondii and Leptospira spp. infection in free-ranging armadillos - da Silva, Rodrigo Costa [UNESP]; Zetun, Carolina Ballarini [UNESP]; Gimenes Bosco, Sandra de Moraes [UNESP]; Bagagli, Eduardo [UNESP]; Rosa, Patricia Sammarco; Langoni, Helio [UNESP] (Elsevier B.V., 2008)
Armadillos are primitive mammals used as food, mostly in rural areas. These animals may be sources of toxoplasmosis and leptospirosis infection for humans, but there is little information about their potential risk as reservoirs. In order to determine the prevalence of armadillos infected by Toxoplasma gondii and Leptospira spp., serum samples of 31 nine-banded armadillos (Dasypus novemcinctus), three six-banded armadillos (Euphractus sexcinctus), two naked-tailed armadillos (Cabassous tatouay) and two long-nosed armadillos (D. hybridus), captured in the mid-west region of the state of São Paulo, were analyzed for leptospirosis using the Microscopic Agglutination Test (MAT-l), and for toxoplasmosis using the Modified Agglutination Test (MAT-t). Only 4/31 (12.90%) nine-banded armadillos were positive for T gondii, while 3/31 (9.68%) nine-banded armadillos and 1/3 (33.33%) six-banded armadillos presented antibodies to Leptospira spp., demonstrating the potential risk of T gondii and Leptospira spp. transmission to humans, mainly due the habit of eating the meat of these animals in rural areas. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Armadillos; Toxoplasma gondii; Leptospira spp.; Serology